Microbiological and physiochemical attributes of hot water sulphur spring of Unkeshwar - P.S Wakte2, D.U Bhusare1* and (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> A water sample was collected from hot sulphur spring of Unkeshwar for microbial and physiochemical study. Water sample is subjected to physiochemical analysis like pH, TDS, conductivity, chlorine, salinity, dissolved oxygen (DO), biological oxygen demand (BOD) and chemical oxygen demand (COD). The BOD and COD were found in lower amount. Four bacterial strains were isolated from the water sample and all they are spore former, gram positive, motile in nature. Among them one bacterial species was identified and confirmed by 16S r-RNA sequencing showed 97 % similarity to Bacillus licheniformis. The identified strain was observed under SEM showed an average length was 1.43 Ã‚Âµm. The optimum pH and temperature for the growth of BWU-1 isolate was 9 and 50Ã‚Â°C. The performed MPN method showed the absence of coliform bacteria in the water sample. The B. licheniformis BWU-1 having potential to produce the hydrolytic enzymes such as protease and amylase were analyzed on SMA and Starch agar plates respectively by observing zone of clearance. Ã‚Â